A comparison of African buffalo, N'Dama and Boran cattle as reservoirs of Trypanosoma congolense for different Glossina species - Moloo, S.K.; Olubayo, R.O.; Kabata, J.M.; Okumu, I.O. (Wiley, 1992)
**Abstract.** Teneral *Glossina morsitans centralis* Machado were fed on the flanks of the African buffalo *(Syncerus coffer* Sparrman), N'Dama *(Bos taurus* L.) or Boran *(Bos indicus* L.) cattle infected with *Trypanosoma congolense* Broden. The infected tsetse were maintained on rabbits and on day 30 after the infected feed, the surviving tsetse were dissected to determine the infection rates. The mean infection rates (%±SE) in the midgut of tsetse fed on buffalo, N'Damas and Borans were 23.5 ± 3.3, 31.6 ± 2.7 and 33.7 ± 4.6, respectively. The differences were not significant. However, the mean mature infection rate in tsetse fed on the buffalo (13.2 ±2.1%) was significantly lower compared to the rates in tsetse fed on the N'Dama (20.4 ± 1.4) or the Boran cattle (21.4 ± 1.1). When groups of teneral *G.m.centralis, G.pallidipes* Austen, *G.p.gambiensis* Vanderplank, *G.f.fuscipes* Newstead, *G.brevipalpis* Newstead and *G.longipennis* Corti were fed simultaneously on either an infected buffalo, an N'Dama or a Boran steer, the mature infection rates ranged from 0 to 16.1%. Irrespective of the host species used, the *T.congolense* infection rate was highest in *G.m.centralis*, lowest in the *palpalis* and *fusca* group tsetse, with *G.pallidipes* being intermediate. Nevertheless, the trypanoresistant African buffalo and N'Dama may serve as reservoirs of *T.congolense* as can trypanosusceptible Boran cattle.